Development of web-based resource usage patterns among English-to-Chinese trainee translators - Yuxing Cai; Vanessa Enríquez Raído (Humanities & Social Sciences Communications)
Abstract The aim of this article was to examine changes in trainee translators’ web-based resource use patterns during a four-month English-to-Chinese translation practice course. An analytical framework was employed to statistically examine resource use development, including new and emerging resources. The research design incorporated four repeated measures with a cohort of 19 participants, and data were collected via the simultaneous use of a key logger and a screen recorder in a remote setting. A quality assessment was conducted to investigate the correlation between resource use and the overall quality of the final translation products. Findings indicate a shift in resource preference from dictionaries to knowledge-based resources, with trainee translators focusing on larger contextual issues rather than lexical problems. The quality assessment revealed a slight negative correlation between the translation error scores and the percentage of time allocated to knowledge-based resources. These findings highlight the importance of understanding trainee translators’ shifting resource use and evaluating their resource competence. The implications of the findings for translator training are discussed, and the need to adapt training programs to meet changing resource landscapes emphasized.